Determinants of utilization of antenatal care and health facility delivery among women in rural part of Delta State, Southern Nigeria (Annals of Medical Research, 2021)
Aim: The study investigated the predictors of a minimum of four ANC visits and health facility delivery among 900 women in eight rural communities in Delta State, Southern Nigeria.Materials and Methods: The study is a cross-sectional community health survey, which used a pretested questionnaire to elicit information on ANC and health facility delivery from 900 women within the reproductive ages. Both predictive and descriptive analyses were undertaken. Analyses were undertaken with Stata 13.0 for windows.Results: Coverage of ANC and health facility delivery was respectively 26.8% and 62.6%. The odds for reporting a minimum of four ANC visits {aOR: 2.68, 95% CI: 0.96-7.47} and having deliveries in health institutions {aOR: 6.46, 95% CI: 1.44 - 28.99} were higher for women who reported the highest income group N (15,000-99,999). Primary educational qualifications {aOR: 1.67, 95% CI: 0.93-3.04} significantly improve the odds for a minimum of four ANC visits. Utilizing ANC from skilled provider {aOR: 3.59, 95% CI: 1.99-6.46} improves the chances for health facility delivery.Conclusion: Raising awareness on the benefit of adequate number of ANC visits and health facility delivery will no doubt increase women’s access to both optimal use of ANC and encourage health facility delivery in rural parts of Nigeria.
Keywords: ANC; health facility delivery; rural women; Nigeria